2008
DOI: 10.1080/10253890701822378
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive response of adult rat Leydig cells to repeated immobilization stress: The role of protein kinase A and steroidogenic acute regulatory protein

Abstract: The ability of immobilization stress (IMO) to decrease Leydig cell steroidogenesis and serum androgen concentration has been previously observed, but the possible mechanism(s) involved in the adaptation to prolonged or repeated stress have not been identified. In this study, we investigated whether the Leydig cells obtained from adult rats subjected to acute (15 min, 30 min or 2 h) and repeated (2 or 10 days, 2 h daily) IMO show adaptive mechanism(s) in response to stress-impaired steroidogenesis. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 40 publications
4
48
0
Order By: Relevance
“…The proportion of Leydig cells present in culture was determined by staining for HSD3B activity (Payne et al, 1980), and was found to be 95.3 ± 2.7%, while the viability was more than 90%. The steroidogenic capacity of Leydig cells (estimated by dose-dependent stimulation with hCG) and the activity of steroidogenic enzymes (estimated by incubating cells with increasing concentrations of steroid substrates), were in line with those previously published by others (Akinbami et al, 1994) as well as our group (Andric et al, 2007(Andric et al, , 2010aKostic et al, 2008Kostic et al, , 2010Kostic et al, , 2011. These data were not showed and served to us just as internal control.…”
Section: Extraction Of Steroids From Testicular Tissuesupporting
confidence: 88%
See 4 more Smart Citations
“…The proportion of Leydig cells present in culture was determined by staining for HSD3B activity (Payne et al, 1980), and was found to be 95.3 ± 2.7%, while the viability was more than 90%. The steroidogenic capacity of Leydig cells (estimated by dose-dependent stimulation with hCG) and the activity of steroidogenic enzymes (estimated by incubating cells with increasing concentrations of steroid substrates), were in line with those previously published by others (Akinbami et al, 1994) as well as our group (Andric et al, 2007(Andric et al, , 2010aKostic et al, 2008Kostic et al, , 2010Kostic et al, , 2011. These data were not showed and served to us just as internal control.…”
Section: Extraction Of Steroids From Testicular Tissuesupporting
confidence: 88%
“…To follow ex vivo steroids production, and the expression of steroidogenic machinery elements (steroidogenic enzymes, proteins related to the steroidogenesis, transcription factors), cAMP signalling elements (ADCY, PRKA subunits, cAMP specific PDEs), cGMP signalling elements (GUCY, PRKG isoforms, cGMP-specific and dual PDEs) and ADRs, we used primary cultures of purified Leydig cells obtained from control and Doxa-treated rats prepared as described previously by our group (Andric et al, 2007(Andric et al, , 2010aKostic et al, 2008Kostic et al, , 2010Kostic et al, , 2011. Primary cultures of purified Leydig cells were prepared from suspensions of interstitial cells.…”
Section: Extraction Of Steroids From Testicular Tissuementioning
confidence: 99%
See 3 more Smart Citations